Response of some vegetative growth ponitars maize zea mays l. To spray potasium and zinc: RANA .R.ARRAK - ريس عراك, رنا (Journal of Kerbala for Agricultural Sciences, 2017)
Field experiment were conducted in autumn season 2015 in Al-wataifia region/Great Mussiab Project on Loamy soil to study the effect of foliar application of 4 levels from potassium fertilizer (0 , 1000 , 2000 , and 4000 mg.L-1) , and 4 levels of Zinc fertilizer ( 0 , 30 , 60 , and 90 mg.L-1) and their interaction on some vegetative growth parameters of zea mays plant (Buhuth 106 variety), the experiment in RCBD with 3 replications and the average value were compared according to LSD test at 5% level , the results shows : Significant differences between K level treatments, the treatment (4000 mg.L-1) significantly increase the average value of plant height , No. of leaves , leaf area , chlorophyll content , shoot dry matter , and NPK absorption in plant with increasing percentage ( 16.15 , 41.8 , 47.58 , 10.13 , 60.24 , 94.96 , 124.46 , and 85.19% respectively compare with control treatment . Zinc treatment ( 90 mg.L-1) increase significantly a parameter above with increasing percentage ( 12.82 , 28.63 , 37.92 , 15.21 , 30.82 , 45.48 , 89.52 , and 61.17% respectively) compare with control treatment , while the interaction treatment ( 4000 mg.L-1 + 90 mg.L-1) increase significantly the growth parameters compared with other interaction treatments.